Romanian athletics in numbers-a brief analysis - Gheorghe LUCACIU (Editura Universităţii din Oradea, 2018)
Sport system is a very complex mechanism whose proper functioning depends on the efficient operation of each component. "Functional requirements (a.n.: of a system) describe the desired end function of a system operating within normal parameters, so as to assure the design is adequate to make the desired product and the end product reaches its potential of the design in order to mett user expectations". 1 The qualitative and quantitative evolution of some aspects that define the organization and functioning of the Romanian athletics system can be viable instruments for determining the potential/resources of evolution, as well as indicators for possible adaptive measures correlated with the tendencies. We have carried out a quantitative analysis of the evolution of some components of Romanian athletics system, of the number of clubs and athletes in the National Athletics Championships (by age/categories and events), the stability of the competitors over several years, and the evolution of recorded performances in order to identify progress and trends. The statistically processed informations, comes from the database of the Romanian Athletics Federation. 2 In this context, we mention that the period covered by the research (2009- 2017) was limited by the limited content of the mentioned electronic archive.